Species are not most abundant in the centre of their geographic range or climatic niche. (12th October 2017) - Dallas, Tad; Decker, Robin R.; Hastings, Alan
Abstract: The pervasive idea that species should be most abundant in the centre of their geographic range or centre of their climatic niche is a key assumption in many existing ecological hypotheses and has been declared a general macroecological rule. However, empirical support for decreasing population abundance with increasing distance from geographic range or climatic niche centre ( distance–abundance relationships) remains fairly weak. We examine over 1400 bird, mammal, fish and tree species to provide a thorough test of distance–abundance relationships, and their associations with species traits and phylogenetic relationships. We failed to detect consistent distance–abundance relationships, and found no association between distance–abundance slope and species traits or phylogenetic relatedness. Together, our analyses suggest that distance–abundance relationships may be rare, difficult to detect, or are an oversimplification of the complex biogeographical forces that determine species spatial abundance patterns.